THEORIES OF LEARNING COGNITIVISM AND ISLAMIC EDUCATION: IMPLICATIONS OF LEARNING COGNITIVISM THEORY IN ISLAMIC EDUCATION - Rizqy Mutmainnah Amin (International Journal of Islamic Studies, 2021)
Cognitive learning theory emphasizes learning is a process that occurs in the human mind. Cognitive learning theory focuses more on the learning process than the learning outcome itself. Learning in this theoretical view does not only involve the relationship between stimulus and response. However, it is an activity that involves complex thought processes. This means that there is complex activity in the individual's brain during the learning process. Therefore, cognitive learning theory believes that learning is a thought process, and focuses more on the learning process itself than learning outcomes. Where in the context of psychology this thought process is referred to as mental activity, and in the context of education is called learning. Knowledge can only be gained through the learning process. Therefore, it is very important to study the position of the human brain here through the thought process. This is why God requires people to learn.